Modulation of host plant immunity by Tobamovirus proteins - Conti, Gabriela; Rodriguez, Maria Cecilia; Venturuzzi, Andrea Laura; Asurmendi, Sebastian (2017)
To establish successful infection, plant viruses produce profound alterations of host physiology, disturbing unrelated endogenous processes and contributing to the development of disease. In tobamoviruses, emerging evidence suggests that viral-encoded proteins display a great variety of functions beyond the canonical roles required for virus structure and replication. Among these, their modulation of host immunity appears to be relevant in infection progression. In this review, some recently described effects on host plant physiology of Tobacco mosaic virus (TMV)- encoded proteins, namely replicase, movement protein (MP) and coat protein (CP), are summarized. The discussion is focused on the effects of each viral component on the modulation of host defense responses, through mechanisms involving hormonal imbalance, innate immunity modulation and antiviral RNA silencing. These effects are described taking into consideration the differential spatial distribution and temporality of viral proteins during the dynamic process of replication and spread of the virus. In discussion of these mechanisms, it is shown that both individual and combined effects of viral encoded proteins contribute to the development of the pathogenesis process, with the host plant’s ability to control infection to some extent potentially advantageous to the invading virus.